2014
DOI: 10.4236/health.2014.614198
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Death Review (MNDR): A Useful Approach to Identifying Appropriate and Effective Maternal and Neonatal Health Initiatives in Bangladesh

Abstract: Objectives: To identify the effects of Maternal and Neonatal Death Review (MNDR) in terms of improving maternal and neonatal health at the community level in Bangladesh. Methods: Both quantitative and qualitative methods were undertaken for collecting data in Kashipur Union, Bangladesh. Death notifications from households, subsequent data collections from a focus-group discussion (FGD), a group discussion (GD) and in-depth interviews (IDIs) were obtained using structured tools and guidelines. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…10 The Directorate General of Health Services (DGHS) in collaboration with the Directorate General of Family Planning (DGFP) conducted the initial piloting of the intervention in the district, Thakurgaon, with technical and implementation support from two non-government organizations, the CIPRB and UNICEF, Bangladesh. The financial supports was provided by Canadian CIDA (DFATD) and initially funded by the Department for International Development (DFID) & European Commission.…”
Section: Introductionmentioning
confidence: 99%
“…10 The Directorate General of Health Services (DGHS) in collaboration with the Directorate General of Family Planning (DGFP) conducted the initial piloting of the intervention in the district, Thakurgaon, with technical and implementation support from two non-government organizations, the CIPRB and UNICEF, Bangladesh. The financial supports was provided by Canadian CIDA (DFATD) and initially funded by the Department for International Development (DFID) & European Commission.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, we clearly demonstrated that only correct knowledge and awareness of actions could help both mother and baby survive. Although a number of initiatives already has been taken by the government to reduce the maternal and neonatal deaths in Bangladesh (23,24), it is important to broaden the focus on other contributing factors that may lead to the death of mother and baby due to, for example, a burn injury. Increasing community awareness and improving knowledge through education and mass media are two methods by which we can disseminate correct messages to help prevent such deaths in future.…”
Section: Discussionmentioning
confidence: 99%
“…MDNRs support the examination of each maternal and neonatal death in the community by performing 'verbal autopsies', which are used to understand the medical causes and contributing factors relating to maternal and neonatal deaths. [20][21][22] Within the MNDR system, the government has also initiated SA as a social intervention.…”
Section: Introductionmentioning
confidence: 99%